Could Reliability Naturally Imply Safety? - Palermos, Spyridon Orestis (European Journal of Philosophy, 2015)
The aim of the present paper is to argue that robust virtue epistemology is correct. That is, a complete account of knowledge is not in need for an additional modal criterion in order to account for knowledge-undermining epistemic luck. I begin by presenting the problems facing robust virtue epistemology by examining two prominent counter examples--the Barney and 'epistemic twin earth' cases. After proposing a way in which virtue epistemology can explain away these two problematic cases, thereby, implying that cognitive abilities are also safe, I offer a naturalistic explanation in support of this last claim, inspired by evolutionary epistemology. Finally, I argue that naturalized epistemology should not be thought of as being exclusively descriptive. On the contrary, the evolutionary story I offer in support of the claim that reliability implies safety can provide us with a plausible epistemic norm.